2021
DOI: 10.1038/s41467-021-25721-1
|View full text |Cite
|
Sign up to set email alerts
|

Pressure induced superconductivity in MnSe

Abstract: The rich phenomena in the FeSe and related compounds have attracted great interests as it provides fertile material to gain further insight into the mechanism of high temperature superconductivity. A natural follow-up work was to look into the possibility of superconductivity in MnSe. We demonstrated in this work that high pressure can effectively suppress the complex magnetic characters of MnSe, and induce superconductivity with Tc ~ 5 K at pressure ~12 GPa confirmed by both magnetic and resistive measurement… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…Furthermore, high-pressure properties of manganese chalcogenides, such as MnSe and MnS 2 , have also attracted attention, since they exhibit large cell volume collapse and spin crossover during pressure-induced phase transitions [ 9 , 10 , 11 ]. Interestingly, a recent study reported the observation of superconductivity with T C ~ 9 K in pressurized MnSe at ~35 GPa [ 12 ]. However, the superconducting structure is not clear yet.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, high-pressure properties of manganese chalcogenides, such as MnSe and MnS 2 , have also attracted attention, since they exhibit large cell volume collapse and spin crossover during pressure-induced phase transitions [ 9 , 10 , 11 ]. Interestingly, a recent study reported the observation of superconductivity with T C ~ 9 K in pressurized MnSe at ~35 GPa [ 12 ]. However, the superconducting structure is not clear yet.…”
Section: Introductionmentioning
confidence: 99%
“…However, the same transition was observed at 140 K during the cooling process performed by means of synchrotron X-ray and neutron diffraction [ 14 ]. Furthermore, experimental works based on the in situ synchrotron XRD pattern [ 12 ] and the in situ angle dispersive synchrotron X-ray diffraction pattern [ 9 ] demonstrated that at room temperature, the low-pressure (LP) (0~12 GPa) and high-pressure (HP) (>30 GPa) phase structures of MnSe are NaCl-type with Fm-3m symmetry and MnP-type with Pnma symmetry, respectively. However, in [ 9 ], it is pointed out that there is an unknown tetrahedral structure between the Fm-3m and Pnma phases.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations